2018
DOI: 10.1002/ajcp.12222
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Parents' Community Connections for Adolescent Well‐being: An Examination of Military Families

Abstract: Drawing from the Social Organization Theory of Action and Change (SOAC), this analysis of 223 military families, including active duty (AD) military and civilian partners, examines how parents' sense of community and community engagement (two elements of community connections) are associated with their own resilient coping, and ultimately with important outcomes capturing their adolescent offspring's individual well-being (depression, anxiety, and self-efficacy) and family well-being (family functioning and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Our research on military members and families has shown that the sense of community is influenced by extent of community participation (e.g., collective events and activities), ease of making connections with others in the community, and a sense of responsibility for others in the community (Bowen, Martin, Mancini, & Nelson, ). Sense of community is measured by self‐reports of feelings of belonging in the community, feeling close to other community members, a feeling that one's own circumstances are similar to others in the community (Mancini, Bowen, Martin, & Ware, ; see O'Neal, Mallette, & Mancini, , for a discussion of the Community Connections Index).…”
Section: Community Social Organization and Multiple Contexts That Surmentioning
confidence: 99%
“…Our research on military members and families has shown that the sense of community is influenced by extent of community participation (e.g., collective events and activities), ease of making connections with others in the community, and a sense of responsibility for others in the community (Bowen, Martin, Mancini, & Nelson, ). Sense of community is measured by self‐reports of feelings of belonging in the community, feeling close to other community members, a feeling that one's own circumstances are similar to others in the community (Mancini, Bowen, Martin, & Ware, ; see O'Neal, Mallette, & Mancini, , for a discussion of the Community Connections Index).…”
Section: Community Social Organization and Multiple Contexts That Surmentioning
confidence: 99%
“…In a qualitative study of civilian spouses, Strong and Lee () found that social support was an integral, and commonly reported, method of coping with a deployment or reintegration, and the support provided by other military families was particularly important. Our earlier research suggests that military parents' sense of community and community engagement are associated with their overall resilient coping abilities, which, in turn, are associated with their adolescent child's well‐being and overall family functioning (O'Neal, Mallette, & Mancini, ). However, this work focused on resilient coping abilities more broadly, rather than identifying coping at a more nuanced level, focused specifically on individuals' abilities to cope with military challenges.…”
Section: Theoretical Perspectives On Contexts Processes and Well‐beingmentioning
confidence: 99%
“…Stepfamilies who perceive higher levels of collective efficacy may experience reductions in parental burden and family stress, resulting in more adaptive and positive family processes. Indeed, neighbors providing support to one another and engaging in the monitoring of youth behavior might help ease tension in couple and parent–child relationships by distributing, at least in part, the load of child‐rearing and other responsibilities (Bowen et al., , ; Deng et al., ; O'Neal et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Stepfamilies who perceive higher levels of collective efficacy may experience reductions in parental burden and family stress, resulting in more adaptive and positive family processes. Indeed, neighbors providing support to one another and engaging in the monitoring of youth behavior might help ease tension in couple and parent-child relationships by distributing, at least in part, the load of child-rearing and other responsibilities (Bowen et al, 2000(Bowen et al, , 2002Deng et al, 2006;O'Neal et al, 2018). From an environmental-stress perspective, stepfamilies who perceive high-quality relationships with neighbors might also worry less about the welfare of their children in the larger environment and ease control over the behavior of adolescent youth (Noah, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation